Systematic Literature Review: Determinants of Mobile Banking Users’ Satisfaction in Indonesia - Eunike Al Grea; Syafrizal Helmi Situmorang; Beby Karina Fawzeea Sembiring (Annals of Management and Organization Research, 2026)
Purpose: This study aims to identify the aspects that affect mobile banking user satisfaction in Indonesia. Research Methodology:  This systematic literature review uses specific keywords to gather relevant articles, sourcing 817 publications from Scopus between 2020 and 2024. The analysis employs the Publish or Perish and VOS Viewer applications through the bibliography coupling method and focuses on literature related to Indonesia. Results: The articles were further evaluated using the Rayyan.ai platform, and 16 articles were identified. The findings reveal several factors influencing mobile banking users’ satisfaction in Indonesia, with service quality, system quality, and information quality being the most prevalent. Several other aspects were also examined in this study. Conclusions: The most affected determinants of mobile banking users’ satisfaction in Indonesia are service quality, system quality, and information quality. Uniquely, although the determinants are similar, each study uses different measurements. Limitations: This study's limitations relate to its focus on mobile banking users in Indonesia, which may yield different results if conducted in other countries. Furthermore, the articles reviewed do not cover all available mobile banking options in Indonesia, where user needs vary, potentially affecting the outcomes. Contributions: The results of this study can be applied in managing banks with digital applications, such as mobile banking, and provide insights for development teams to enhance features and improve user satisfaction.